Formulation and Physical Evaluation of a Combination of Pegagan Leaf Extract (Centella Asiatica L. Urb) and Patchouli Oil (Patchouli Oil) in Liquid Body Wash Preparation - Sari, Dwi Maya Ratna; Fanani, Zaenal; Khudzaifi, Muhammad (Advances in Healthcare Research, 2025)
Purpose: This study aimed to formulate and evaluate the physical quality of liquid body wash containing Centella asiatica (L.). Urb. Extract and patchouli oil to determine the optimal concentration for safe and effective use, with the hypothesis that varying concentrations would affect pH, viscosity, foam stability, and overall product quality. Research Method: An experimental post-test control design was conducted at the Pharmaceutical Technology Laboratory of Cendekia Utama Kudus Health Technology Institute, with irritation tests performed at Universitas Muhammadiyah Kudus. Four formulations (F0–F3) contained pegagan extract (0%, 5%, 10%, 15%) and patchouli oil (0%, 1%, 2%, 3%). Physical evaluations included organoleptic, homogeneity, pH, viscosity, foam height, and irritation tests. Data were analyzed using Shapiro-Wilk, Levene’s test, and One-Way ANOVA. Results and Discussion: All formulations met SNI standards for liquid soap. Formula 1 (5% extract, 1% patchouli oil) exhibited the most balanced properties, with a neutral pH (6.06), suitable viscosity (695 mPas), stable foam height (13.50 mm), and no irritation. Higher extract concentrations reduced viscosity but did not significantly affect foam height. No formula caused redness or itching in volunteers. Implications: Formula 1 is recommended for further development as a natural, skin-safe liquid body wash. Future studies should assess the long-term stability, consumer acceptance, and commercial feasibility of these products.